THE IMPACT OF CELEBRITY ENDORSEMENT ON CONSUMER BUYING BEHAVIOR - QURESHI, MUHAMMAD MEHTAB; MALIK, HUMAIRA MANSOOR (Advances in Social Sciences Research Journal, 2017)
The purpose of this study is to explore the impact of celebrity endorsement on consumer’s buying intentions. This study concentrated on discovering the thoughts of Pakistani customers about celebrity endorsement by analyzing the different characteristics of the celebrity endorsement with respect to consumer’s buying intentions. In this study we reviewed the former literature present on the topic of celebrity endorsement. That gives clear perception of different important prospects regarding this topic. In order to discover the impact of different attributes of celebrity on consumer buying behavior quantitative approach is applied. The data has been collected from 150 respondents with the help of structured questionnaire and analyzed by using software SPSS. It was find that some aspects of celerity endorsement like gender, attractiveness, credibility, endorser type & multiple celerity endorsement proved to be effective with respect to buying intentions while multiple product endorsement has negative relationship with consumer buying behavior. In the end the study proves that the overall impact of celebrity endorsement on consumer’s buying intentions is positive. Keywords: Celebrity endorsement, Celebrity endorser, Purchase intentions, Consumer buying behavior, Celebrity endorsement in Pakistan